Exploring Teachers’ Challenges And Needs In Supporting Inclusive Education For Students With Emotional Or Behavioral Disorders - Dewi, Nastitisari; Supena, Asep; Bintoro, Totok; Edwita, Edwita; Yatimah, Durotul (Universitas Pakuan, 2025)
This study aims to analyze the challenges and needs of teachers in handling students with emotional or behavioral disorders at SDN Benteng 3, Sukabumi City. Emotional or behavioral disorders in students pose significant challenges for teachers, as difficulties in understanding and managing such behaviors can impact the effectiveness of teaching and well-being of both teachers and students. Using a qualitative field study approach, this research explores the perceptions, barriers, and needs expressed by teachers. Data were collected through in depth interviews, observations, and document analysis. Participants included 16 teachers from SDN Benteng 3, comprising 12 classroom teachers adn 4 subject teachers in Islamic education and Physical Education, as well as students identified with emotional or behavioral disorders. The findings indicate several obstacles, such as limited knowledge about emotional or behavioral disorders in students, a lack of specialized training, and minimal institutional support. Teachers highlighted the need for additional training, specialized teaching strategies, and supportive facilities for implementing inclusive education. These findings underscore the importance of targeted interventions and institutional education to enchance teachers capacities in inclusive education. This study is expected to serve as a foundation for developing training programs and policies that support teachers in implementing inclusive education